In Council, Philadelphia, June 1, 1780 : Sir, The Continental Army, upon which our prospects of safety and liberty so much depend, have, by various disappointments, been reduced to great distress for want of provisions . ([Printed by Francis Bailey?], 1780)
Council's request for meat for the troops and the procedure to be used when so obtaining these provisions.